Determinants of farmers' adoption of Clearfield production system in Malaysia - Terano, Rika; Mohamed, Zainal Abidin; Zanul Din @ Zainuddin, Nur Syuhada (Elsevier, 2016)
The weedy rice is one of the serious problems causing lower yield of paddy/rice production. In order to solve the weedy paddy/rice problem new herbicide-resistant paddy/rice variety was introduced in 2003. Although the new herbicide-resistant paddy/rice varieties have been scientifically proven as a good solution to manage weedy rice, however there is list of procedure that the farmers has to follows, which sometime is quite difficult for them to do so. Thus it is inevitable from the socio-economic aspect to investigate the opinion of paddy/rice farmers towards using the new herbicide-resistant paddy/rice known as Clearfield Technique (CLRS) as their farming systems. Exploratory Factor Analysis (EFA) and the Binary Logit regression were being employed as the methodology to analyze the data. The EFA analysis shows that the dimension of farmers opinion towards using CLRS such as effective controlling of weeds, increase production yield, government initiative and farmers’ knowledge as the determinant for adopting CLRS.